O Gato e o Escuro, de Mia Couto: «uma estória por via da poesia» - Albuquerque, Fátima (2004)
In O Gato e o Escuro, Mia Couto used a very complex literary model, of a hybrid nature, to tell his ‘story’. Resorting to several structural elements of poetry, he organized a text where many usual symbols of Children Literature clustered around myths of transformation, created a very rich literary idiolect.